MoS2 nanosheets inlaid in 3D fibrous N-doped carbon spheres for lithium-ion batteries and electrocatalytic hydrogen evolution reaction. (September 2019) - Wang, Xin; Fei, Siming; Huang, Shoushuang; Wu, Chenghao; Zhao, Junru; Chen, Zhiwen; Uvdal, Kajsa; Hu, Zhangjun
Abstract: Molybdenum disulfide (MoS2 ) has received considerable interests in rechargeable lithium-ion batteries (LIBs) and hydrogen evolution reaction (HER). To overcome the instinct limitations of pristine MoS2, such as low conductivity, poor cyclic stability and rate performance, hybrid carbon-MoS2 composites are often practically applied to improve the electrochemical properties. Herein, a facile, scalable, and durable synthesis method is innovated to inlay MoS2 nanosheets into three-dimensional (3D) fibrous nitrogen-doped carbon spheres (FNCs) for achieving 3D FNC-MoS2 composites. The free-standing 3D FNC-MoS2 nanocomposites can be used as the anode for LIBs. It exhibits a high reversible capacity of ∼700 mA h g −1, and nearly no fading of the capacity nearly after 400 cycles at a current density of 1.2 A g −1 . Meanwhile, FNC-MoS2 exhibits superior HER activity accompanied by a small overpotential of around 194 mV in 0.5 M H2 SO4 . Tafel slopes are estimated to be 54 mV dec −1, and the current density of FNC-MoS2 decreases very slightly compared to the initial one after 1000 cycles. We are convinced that the enhanced Li + storage performance and HER activity are attributed to the synergistic effects and structural advantages, such as higher specific surface, larger pore volume, radical fibrous structure, and chemical/mechanical stability, achieved from the unique architectures of the title material. Graphical abstract: Image 1